Socioeconomic and demographic predictors of extracurricular achievements among UK medical students (FAST study) - Jessica Lo; Anna Collins; Sophie West; Daniel MaGee; Sara Ali; Tomas Ferreira; Anson Wong; Kavyesh Vivek; Freya F Semple; Benjamin French; Riya Patel; Guilherme Movio; et al. (BMJ Open)
Objective To investigate the relationship between demographic characteristics and extracurricular achievements among UK medical students.Design National, cross-sectional survey.Setting All 44 UK medical schools recognised by the General Medical Council.Participants 8,395 medical students.Outcomes Binary indicators of extracurricular engagement, including PubMed-indexed authorship, academic presentations, quality improvement projects, leadership roles and academic prizes. Logistic regression models were used to explore associations with demographic and extracurricular achievement predictors.Results Logistic regression analysis showed that students from private schools (OR 1.35, CI 1.20 to 1.53, p<0.0001) and those with a parent or sibling in medicine (OR 1.38, CI 1.12 to 1.69, p=0.002) had notably higher odds of participation in research. Ethnic disparities in raw extracurricular attainment were evident, but largely disappeared when adjusting for other predictors. Males were more likely to hold leadership roles and deliver oral presentations, but no gender differences were seen in publication rates.Conclusions Significant disparities in extracurricular achievement exist among UK medical students, principally associated with gender, private schooling and familial links to medicine. Apparent ethnic differences were largely attenuated after adjustment for other variables, indicating socioeconomic factors as stronger predictors of engagement. Given the role of these achievements in postgraduate selection, targeted interventions by medical schools and professional bodies to widen access to funding, mentorship and structured guidance for all students, regardless of perceived advantage, may support equitable opportunity without undermining merit-based standards.